(untitled) (The Journal of Psychology and Sociology, 2025)
According to global ethical principles of social work, social workers are called upon to challenge stigmatization, discrimination, oppression and violation of human rights in all forms. Considering Kazakhstan’s unique cultural context, Social Work faces challenges related to the need to integrate Global professional standards and local socio-cultural norms. In this regard, critical theory and critical reflection are becoming the most important components of social worker training. This research aims to analyze the integration of critical theories and the development of critical reflection in educational programs on social work in Kazakhstan, with an emphasis on emerging ethical contradictions and strategies used by teachers. The study involved 14 teachers (n=14) from seven universities in Kazakhstan. The methods of in-depth interviews and reflective thematic analysis were used. Analysis of qualitative data has shown that critical theories are applied fragmentally and often intuitively, while feminist theory is the most recognizable. According to the teachers, the discussion of stigmatization, discrimination and gender inequality is actively supported, while the topics of power and hierarchy are perceived by them as politicized and irrelevant for social work. In addition, the concepts of critical thinking and critical reflection are confused. The authors emphasize the need for institutional support and improving the competence of social work teachers for the systematic implementation of critical education, contributing to the formation of social sensitivity and professional self-awareness of future social workers. The conducted research contributes to the development of the theoretical and methodological base of critically oriented social work education in Kazakhstan. The practical significance of the results lies in the possibility of their use in the development of curricula, teacher training and the formation of educational policy in the field of social work in Kazakhstan and other countries with a similar cultural context. Key words: critical reflection, critical theory, social work education, professional ethics, social justice, cultural values.